PROGRAM REHABILITASI DAN PELESTARIAN TANAMAN CENDANA DINAS KEHUTANAN KABUPATEN BELU PROPINSI NUSA TENGGARA TIMUR DALAM TELAAH UNDANG-UNDANG NOMOR 32 TAHUN 2009 - Elias Frederikus Kelen (UPPM, 2018)
The research that included in normative legal research, discusses about Cendana’srehabilitation and conservation programm. Researcher uses the induction analyzespeculativemethod to analyze the effectivity of work by the Forest Departement programm.Beside of the first purpose as a tool to keep the living-space to save, that programm also givepeople the good life to living.Cendana (Santalum Album) is one of plants that grows naturally in East LesserSundas. Many people like this plant because there are many usefull that including bycendana. The risk also equallity. A big eksploitation that included illegal logging is a real factthat familiar to us. The missunderstanding to this problem will gives a ekstra effect to theTimor Island identity of cendana.This forest rehabilitation is also a next programm that explisit in law language onIndonesian Regulation Number 32/2009 about Protection and Management of Living-Space.The information in environmental law also give the same sentence that protection andconservation to environment is just not a governance homework, or make a proff by effectivityin Forest Department programm but this is our homework. It means that a lot people have aduty to keep and protect them.